Analiza medsebojnih izvoznih vzorcev majhnih držav Evropske unije (EU-27) z analizo omrežij - Rašković, Matevž (IB revija (Ljubljana), 2012)
This paper employs a network analysis approach, and outlines the usefulness and complementarity of network analysis; vis-a-vis traditional neoclassical analytical approaches (gravity models, econometric models etc.), which are usually applied to the analysis of inter-country export flows. It analyzes the patterns of inter-country EU-27 member states with the help of three new weighted centrality measures, related to degree, closeness and betweenness centrality; as recently published in the Social networks journal. Particular attention is also paid to the issue of export patterns of small EU-27 member states, with up to 5 million inhabitants. Our analysis shows that within an inter-country EU-27 export network, small states in most cases do not tend to geographically concentrate their exports to neighbouring EU markets, if we take into account the number of their immediate EU-27 neighbours. Thus, the alleged geographical export concentration of small EU-27 member states appears to have more to do with their geographical position and the number of EU neighbours, and less with their small size per se. In terms of the structural position of particular EU-27 small member states, betweenness centrality reveals how Estonia's high betweenness centrality shows its unique role in the network. In this network, Estonia acts as an important export "interface" between the developed Scandinavian markets and key continental European markets. The visualization of the inter-country EU-27 export network also reveals a clear core-periphery structure, with two additional cliques.
Keywords: European Union; Evropska unija; Export; Izvoz; Male države; Small states; Analiza omrežij; Network analysis; analize